1997
DOI: 10.1200/jco.1997.15.2.574
|View full text |Cite
|
Sign up to set email alerts
|

Ewing's sarcoma of soft tissues in childhood: a report from the Intergroup Rhabdomyosarcoma Study, 1972 to 1991.

Abstract: This series indicated that EOE in children is similar to rhabdomyosarcoma (RMS) in its response to multimodal treatment. No benefit was apparent from the addition of DOX to VAC chemotherapy in patients with gross residual EOE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
132
1
8

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 214 publications
(149 citation statements)
references
References 24 publications
8
132
1
8
Order By: Relevance
“…Ekstraskeletalni Ewing-ov sarkom je veoma rijedak tumor, koji tipično nastaje u mekom tkivu grudnog koša ili ekstremiteta. Dominantno se javlja kod adolescenata i osoba starosti do 30 godina [1,4,7,8]. Ewing-ov sarkom čini 15% od svih primarnih tumora torakalnog zida [9].…”
Section: Diskusijaunclassified
See 3 more Smart Citations
“…Ekstraskeletalni Ewing-ov sarkom je veoma rijedak tumor, koji tipično nastaje u mekom tkivu grudnog koša ili ekstremiteta. Dominantno se javlja kod adolescenata i osoba starosti do 30 godina [1,4,7,8]. Ewing-ov sarkom čini 15% od svih primarnih tumora torakalnog zida [9].…”
Section: Diskusijaunclassified
“…MR je pouzdaniji u analizi invazije torakalnog zida, dok je CT senzitivniji za male plućne metastaze [7,[10][11][12]. MR, CT i PET/ CT imaju dopunsku ulogu u procjenjivanju lokalne tumorske proširenosti i resektabilnosti te u procjeni diseminacije ovog oboljenja [7,8,10,16]. Uznapredovale forme tumora difuzno metastaziraju, najčešće u pluća i kosti (40-80%).…”
Section: Diskusijaunclassified
See 2 more Smart Citations
“…[1][2][3] In the past decade, ESFT outcome was improved largely through a multidisciplinary strategy based on surgery, radiotherapy and intensified chemotherapy regimens, [4][5][6] whereas large studies have identified risk factors associated with the worse prognosis. [4][5][6][7][8] Since the late 1980s, high-dose chemotherapy (HDC), followed by stem-cell rescue, has been proposed to improve the outcome of patients with poor-prognosis ESFT. Although many studies have been published, the role of HDC in ESFT remains unclear.…”
Section: Introductionmentioning
confidence: 99%